2011
DOI: 10.1016/j.jcrs.2011.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Single perioperative subconjunctival steroid depot versus postoperative steroid eyedrops to prevent intraocular inflammation and macular edema after cataract surgery

Abstract: A single subconjunctival betamethasone acetate injection appears to be a useful alternative to prolonged postoperative administration of dexamethasone eyedrops in controlling intraocular inflammation and development of macular edema after phacoemulsification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 33 publications
1
38
1
Order By: Relevance
“…18 In previous studies, including one of 400 eyes, TA was shown not to differ from PA in postoperative intraocular pressure or incidence of postoperative inflammation 19,20 or macular edema. 21 We found no evidence that injected TA depot is less effective than topical administration of PA alone, although the number of macular edema cases with injected TA was small and the confidence intervals were wide. Injection appears to be safe, as well; we found no diagnoses of globe perforation and no increase in the risk of postoperative (“rebound”) iritis or differences in IOP spikes in the late postoperative period.…”
Section: Discussioncontrasting
confidence: 56%
“…18 In previous studies, including one of 400 eyes, TA was shown not to differ from PA in postoperative intraocular pressure or incidence of postoperative inflammation 19,20 or macular edema. 21 We found no evidence that injected TA depot is less effective than topical administration of PA alone, although the number of macular edema cases with injected TA was small and the confidence intervals were wide. Injection appears to be safe, as well; we found no diagnoses of globe perforation and no increase in the risk of postoperative (“rebound”) iritis or differences in IOP spikes in the late postoperative period.…”
Section: Discussioncontrasting
confidence: 56%
“…The periocular drug delivery system can release dexamethasone sodium phosphate in a time-dependent manner in vitro in the 2 mg/ml and 5 mg/ml groups in vitro. In this study, we set the subconjunctival injection of DEXP as control group for subconjunctival injection is the easiest and most popular method among periocular injection routes applied by the ophthalmologists (Bali et al, 2010;Dieleman et al, 2011;Manandhar, 2011). However, in this study, DEXP can just persist in the eye for no longer than three days after subconjunctival injection, as no DEXP was detected in the eye three days after subconjunctival injection.…”
Section: Discussionmentioning
confidence: 95%
“…OCT images were generated with the use of six radial-line scans, 6.00 mm each in length. The maximal foveal center point thickness (in micrometers) was measured at the center point of the fovea by manually placing computerized calipers at the vitreous-retina and retina-retinal pigment epithelium interfaces [5, 17]. …”
Section: Methodsmentioning
confidence: 99%
“…Macular edema was defined as an increase in the center point thickness of more than 30% from preoperative baseline on OCT 4 weeks after cataract surgery [5, 17]. All patients were divided into either the macular edema group [ME (+)] or nonmacular edema group [ME (−)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation